Psychometric Properties of the Health Assessment Questionnaire Disability Index (HAQ-DI) and the Modified Health Assessment Questionnaire (MHAQ) in Patients with Knee Osteoarthritis - Serdal Kenan Köse; Derya Öztuna; Şehim Kutlay; Atilla Halil Elhan; Alan Tennant; Ayşe Adile Küçükdeveci (Archives of Rheumatology, 2010)
Objective: To investigate the psychometric properties of the Health Assessment Questionnaire Disability Index (HAQ-DI) and the modified HAQ (MHAQ) in patients with knee osteoarthritis (OA). Materials and Methods: The internal construct validity of the HAQ-DI and MHAQ were assessed by Rasch analysis and external construct validity by associations with the Western Ontario and McMaster Universities Index of Osteoarthritis Index (WOMAC), the World Health Organization Disability Assessment Schedule (WHODAS-II) and the Nottingham Health Profile (NHP). Reliability was tested by internal consistency and person separation index. Results: Two hundred and fifteen outpatients with knee OA (mean age±standard deviation (SD) 57.7±10.9 years; 81% female) filled in the assessment scales including HAQ-DI, WOMAC, WHODAS-II and the NHP. MHAQ was not administered as a separate measure but scored by using the HAQ-DI forms. Both the HAQ-DI and the MHAQ data satisfied Rasch model expectations with a mean item fit of 0.096 (SD 1.186) and -0.312 (SD 1.063), and person fit of 0.307 (SD 0.895) and -0.329 (SD 0.879), respectively. Both scales were unidimensional and showed no differential item functioning. The reliabilities of both scales were good with high Cronbach’s alpha and PSI levels above 0.85. However neither of them was particularly well targeted to the current population who displayed a level of disability much below the average difficulty level of the scales. External construct validity was confirmed by expected correlations with WOMAC, WHODAS-II and NHP. Although the distribution of both scales was right skewed, the floor effect was more prominent in MHAQ. Conclusion: Both the HAQ-DI and MHAQ are found to be reliable and valid to assess physical disability in patients with knee OA. However, the possible floor effect in this diagnostic group should be kept in mind. (Turk J Rheumatol 2010; 25: 147-55)